Integrating Technology in Government Internal Audit: Catalysts and Challenges - Nor Syafiqah Ahmad Ramli; Nor Aishah Mohd Ali (Information Management and Business Review, 2024)
In an era marked by digital transformation, various sectors, including government entities, are reevaluating their operational methodologies. This research delves into the pivotal elements influencing the adoption of Information Technology (IT) within the internal audit departments of governmental agencies. The study is grounded in detailed interviews conducted at three distinct government organizations, revealing the intricate dynamics of incentives, barriers, and the prospective benefits associated with IT integration. Preliminary results suggest that a myriad of factors critically shape the strategy toward IT implementation. These include the anticipated enhancements in audit efficiency and effectiveness due to IT adoption, the level of support from senior management, budgetary constraints, and the lack of specialized IT expertise. The findings offer insightful recommendations for government bodies, aiming to aid them in navigating the complexities of IT integration. This study not only highlights the significant role of supportive leadership and resource allocation in facilitating IT adoption but also underscores the need for skill development in this domain. Ultimately, it serves as a strategic guide for government agencies to optimize their auditing processes through effective IT integration.